If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -3x = 0 Combine like terms: 9x + -3x = 6x 6x = 0 Solving 6x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '6'. x = 0 Simplifying x = 0
| r/6=-12 | | 3-18=3z | | 31/3/15/12= | | X^2-10=-9 | | 294.22/4.7 | | u^5+17u^4+80u^3= | | x/(-8)=6 | | f-7=-35 | | c/16=-1 | | -9(-4)+7=25+2(-4) | | y=0.6x+3 | | n/3+16=20 | | x^2-1/4x-3/64=0 | | 7w-49+6w+30=26 | | -7(x+3)+9=-12 | | s/3=-12 | | Y=3(x^2+5)(x^2-2) | | 7x-10=-14 | | -16h= | | 8-9=-31 | | 5x-7-3x=3x-1 | | 10x+3-4x+4=-2x+7x | | x-8.8=-6.5 | | W/7+3-1 | | 5+2(5x-6)=7-5(2x+1) | | d^2-c^4= | | 8y+3(y-6)=4(y+2)-4 | | 31.5/19 | | -2(3(-5)+7)=-3(2(-5)+8) | | -2x-6=-6x-2 | | m+25=24 | | u/-4=14 |